2012
DOI: 10.1016/j.jbiomech.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer counts and raw acceleration output in relation to mechanical loading

Abstract: The purpose of this study was to assess the relationship of accelerometer output, in counts (ActiGraph GT1M) and as raw accelerations (ActiGraph GT3X+ and GENEA), with ground reaction force (GRF) in adults. Ten participants (age: 29.4 ± 8.2 yr, mass: 74.3 ± 9.8 kg, height: 1.76 ± 0.09 m) performed eight trials each of: slow walking, brisk walking, slow running, faster running and box drops. GRF data were collected for one step per trial (walking and running) using a force plate. Low jumps and higher jumps (one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 31 publications
9
122
4
Order By: Relevance
“…The fact that jump-float serving could not be differentiated from sprinting or side-to-side shuffle steps using PVA is most likely due to true similarities in PVA for these movements. These results are supported by findings in a previously performed biomechanical study on PVA and ground reaction force, where jogging and running could not be separated from jumping using differences in PVA (Rowlands & Stiles, 2012). The fact that variance of PRA follows a similar pattern to that of PVA (Figure 2) is consistent with findings in the same study.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that jump-float serving could not be differentiated from sprinting or side-to-side shuffle steps using PVA is most likely due to true similarities in PVA for these movements. These results are supported by findings in a previously performed biomechanical study on PVA and ground reaction force, where jogging and running could not be separated from jumping using differences in PVA (Rowlands & Stiles, 2012). The fact that variance of PRA follows a similar pattern to that of PVA (Figure 2) is consistent with findings in the same study.…”
Section: Discussionsupporting
confidence: 91%
“…This analysis showed that peak segmental accelerations, regardless of accelerometer location, were strongest related to CoM acceleration from the 10-50% of the stance phase. Peak segmental accelerations, which previously have been used to investigate whole-body mechanical loading in daily life activities 7,8 or as in this and previously studies to validate whole-body loading from bodyworn accelerometry 5,6 , can therefore describe only part of the loading the body's soft tissues is exposed to during foot-ground-contact. Trying to use peak segmental accelerations to understand whole-body mechanical loading during foot-ground-contact in team sport movements could therefore be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerometers located at the hip have for example demonstrated an acceptable association with the external forces acting on the whole body, biomechanically expressed as the ground reaction forces (GRF), during daily life activities 7,8 . In addition accelerometers located at the hip and tibia have shown a strong association with GRF in vertical jumping 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The present research utilised the direct dynamic method approach based on a point mass body model: the CM, estimated at the L4-L5 spine level to estimate the actuating forces generated when executing the analysed vertical jumping tasks (Kibele, 1998;Linthorne, 2001). The utilisation of several IU devices to assess different biomechanical variables of vertical jumping has been widely reported in the literature, demonstrating its internal validity and agreement with the gold standard (Bonnet et al, 2013;Requena et al, 2012;Rowlands & Stiles, 2012). Furthermore, using a similar methodology with respect to placing the IU at the mid lumbar spine level of the body, previous studies have also found significant correlations between the biomechanical parameters of jumping measured by IUs and force plates (Choukou et al, 2014;Requena et al, 2012;Rowlands & Stiles, 2012).…”
Section: Discussionmentioning
confidence: 80%